2017
DOI: 10.7874/jao.2017.21.2.107
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Auditory Neuropathy Caused by Pontine Hemorrhage in an Adult

Abstract: A pontine hemorrhage can evoke several neurological symptoms because the pons contains various nuclei and nerve fibers. Hearing loss can develop as a result of a pontine hemorrhage because there is an auditory conduction pathway in the cochlear nucleus of the pons. However, very few cases of hearing loss caused by pontine lesions have been reported, and there have been no reports of auditory neuropathy that developed following a pontine hemorrhage. Recently we had a patient who experienced a nontraumatic ponti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…With regard to etiology, Kim et al proposed that the pontine hematoma injured the bilateral cochlear nuclei and trapezoid body, [10] while Chung et al reported that the hematoma and surrounding edema compressed the bilateral cochlear nuclei. [9] Compared to previous reports, the present case was characterized by the small hematoma volume and the absence of concurrent disturbance of consciousness at hemorrhage onset. Furthermore, in the present patient, bilateral hearing loss began on the day of hospital admission, which is earlier than in previous reports (Table 2).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…With regard to etiology, Kim et al proposed that the pontine hematoma injured the bilateral cochlear nuclei and trapezoid body, [10] while Chung et al reported that the hematoma and surrounding edema compressed the bilateral cochlear nuclei. [9] Compared to previous reports, the present case was characterized by the small hematoma volume and the absence of concurrent disturbance of consciousness at hemorrhage onset. Furthermore, in the present patient, bilateral hearing loss began on the day of hospital admission, which is earlier than in previous reports (Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…However, in cases of major hemorrhage that extends across the bilateral cochlear nuclei, hearing loss accompanied by disturbance of consciousness due to damage to the reticular formation may occur. [9] In such cases, disturbance of consciousness is likely to prevent patients reporting the hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In specific, various forms of hearing loss have been reported in cases of pontine infarction. Bilateral hearing loss has been documented, as well as cases where hearing loss occurs on the opposite side of the pontine infarction according to central auditory pathway [6,12,13,15]. In addition, cases of hearing loss associated with pontine lesions have been reported to exhibit characteristics similar to auditory neuropathy spectrum disorder, where OAE are present but auditory brainstem response is absent, indicating preserved cochlear function [15].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral hearing loss has been documented, as well as cases where hearing loss occurs on the opposite side of the pontine infarction according to central auditory pathway [6,12,13,15]. In addition, cases of hearing loss associated with pontine lesions have been reported to exhibit characteristics similar to auditory neuropathy spectrum disorder, where OAE are present but auditory brainstem response is absent, indicating preserved cochlear function [15]. In this case, the patient presented with silent pontine infarction, exhibiting ipsilateral hearing loss and dizziness, without any other neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%